Indie VisionariesAdvancing the Digital Frontier of Literary Journalism in India - Dowling, David O.; Subin, Paul (Taylor & Francis, 2022)
In recent years, India has seen a new wave of English-language narrative/literary journalism startups, many positioning themselves with ambitious, optimistic editorial mission statements that read like manifestos bent on revolutionizing conventional mainstream media. Through case studies centering on The Caravan, Peepli, and Scroll, this chapter explores the digital publishing industry’s technologies, competing business models, and news brands that constitute narrative longform journalism in India today. Methodologically, close analytical readings of multimodal texts and paratexts situate these publications industrially and culturally. Special attention is paid to the change in India’s digital ecosystem that has opened new spaces for independent journalism startups online, particularly those focusing on longer, textured narratives supported by embedded multimedia interactives, videos, and graphics. The cases exemplify India’s pivot toward immersive narrative longform journalism, a change that now occurs across media. Typologies of digital startups and entrepreneurial journalism theoretically frame this examination of online narrative journalism at the leading edge of independent slow media in India.
Keywords: 33 Ciencias Tecnológicas::3329 Planificación urbana::3329.02 Comunicaciones; ODS 4 - Educación de calidad